2015
DOI: 10.3389/fpubh.2015.00047
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Depressive Symptoms and Physical Diseases in Switzerland: A Cross-Sectional General Population Study

Abstract: Objective: To estimate the association between depressive symptoms and physical diseases in Switzerland, as respective findings might inform about future estimates of mental and physical health care costs.Methods: A population-based study, using data from the Swiss Health Survey collected by computer-assisted telephone interviews and additional written questionnaires during the year 2007 (n = 18,760) in Switzerland. The multistage stratified random sample included subjects aged 15 years and older, living in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 76 publications
1
7
1
4
Order By: Relevance
“…Our results contribute to previous findings on mental-physical comorbidity mostly resulting from association studies in clinical or population-based samples in adults and documenting comprising relationships between mental disorders and physical diseases [ 3 , 5 , 6 ], including the comorbidity patterns observed in the present study [ 65 70 ]. However, as yet, there has been no evidence suggesting a link between substance use disorders and allergies [ 71 ], and even though comorbidity between epilepsy and mental disorders has been described in children [ 28 , 30 ], epidemiological data on the co-occurrence of epilepsy and eating disorders are lacking.…”
Section: Discussionsupporting
confidence: 89%
“…Our results contribute to previous findings on mental-physical comorbidity mostly resulting from association studies in clinical or population-based samples in adults and documenting comprising relationships between mental disorders and physical diseases [ 3 , 5 , 6 ], including the comorbidity patterns observed in the present study [ 65 70 ]. However, as yet, there has been no evidence suggesting a link between substance use disorders and allergies [ 71 ], and even though comorbidity between epilepsy and mental disorders has been described in children [ 28 , 30 ], epidemiological data on the co-occurrence of epilepsy and eating disorders are lacking.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have reported an association between higher levels of depression and the presence of MCDs [ 10 , 11 , 15 , 17 , 19 ]. For example, the results from a US study conducted through telephone interviews indicated that multiple chronic conditions, particularly pulmonary diseases, increased the risk of depression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MCDs and the management of these conditions has become an important public health issue [ 13 16 ]. Up to date, several studies have investigated the impact of MCDs on depression, as well as the relationship between specific chronic diseases and depression [ 3 , 15 , 17 , 18 ]. However, few studies have targeted middle-aged or younger populations compared with elderly populations [ 1 , 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most likely reason for this is that chronic diseases cause the individual to lose physical strength and vigor. Physical diseases also resulted in depressive symptoms [ 22 , 23 ] and generally contributed to the decline of physical and MH. We found, as have other investigators in previous studies, [ 21 , 24 , 25 ] that when caregivers’ income increased, their physical and mental QOL also improved.…”
Section: Discussionmentioning
confidence: 99%